THE EFFECT OF LIQUIDITY, LEVERAGE, AND CAPITAL INTENSITY ON TAX AVOIDANCE WITH COMPANY SIZE AS A MODERATING VARIABLE (CASE STUDY OF ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2020-2023) - Mardhiyatan, Lifit Nur; Rahayu, Sri; Erwati, Misni (Accounting Studies and Tax Journal (COUNT), 2025)
Tax avoidance practices and the factors that influence them, especially liquidity, leverage, and capital intensity with company size as a moderating variable are the main focus of this study. By utilizing secondary data sourced from the publication of financial reports and annual reports of Energy Sector business entities listed on the Indonesia Stock Exchange during the 2020-2023 period, a comprehensive analysis was conducted using SPSS software version 29. The research findings reveal that there is no significant effect between liquidity and tax avoidance strategies, in contrast to leverage which shows a significant impact on tax avoidance activities. Meanwhile, capital intensity does not show a significant effect on tax avoidance behavior. In the context of the role of moderation, company dimensions fail to moderate the relationship between liquidity and tax avoidance practices, as well as the relationship between leverage and tax avoidance efforts. However, company size is proven to be effective as a moderating variable in the relationship between capital intensity and tax avoidance strategies. The results of this investigation contribute valuable perspectives on the determinants of tax avoidance behavior in energy sector corporations in Indonesia and enrich the literature on corporate tax practices in developing economies.